Fire regimes of Australia: a pyrogeographic model system. (25th January 2013) - Murphy, Brett P.; Bradstock, Ross A.; Boer, Matthias M.; Carter, John; Cary, Geoffrey J.; Cochrane, Mark A.; Fensham, Roderick J.; Russell‐Smith, Jeremy; Williamson, Grant J.; Bowman, David M. J. S.; Ladiges, Pauline
Abstract Aim Comparative analyses of fire regimes at large geographical scales can potentially identify ecological and climatic controls of fire. Here we describe Australia's broad fire regimes, and explore interrelationships and trade‐offs between fire regime components. We postulate that fire regime patterns will be governed by trade‐offs between moisture, productivity, fire frequency and fire intensity. Location Australia. Methods We reclassified a vegetation map of Australia, defining classes based on typical fuel and fire types. Classes were intersected with a climate classification to derive a map of 'fire regime niches'. Using expert elicitation and a literature search, we validated each niche and characterized typical and extreme fire intensities and return intervals. Satellite‐derived active fire detections were used to determine seasonal patterns of fire activity. Results Fire regime characteristics are closely related to the latitudinal gradient in summer monsoon activity. Frequent low‐intensity fires occur in the monsoonal north, and infrequent, high‐intensity fires in the temperate south, demonstrating a trade‐off between frequency and intensity: that is, very high‐intensity fires are only associated with very low‐frequency fire regimes in the high biomass eucalypt forests of southern Australia. While these forests occasionally experience extremely intense fires (> 50, 000 kW m−1), such regimes are exceptional, with most of the continent dominated by grass fuels, typically burning with lower intensity (< 5000 kW m−1). Main conclusions Australia's fire regimes exhibit a coherent pattern of frequent, grass‐fuelled fires in many differing vegetation types. While eucalypts are a quintessential Australian entity, their contribution as a dominant driver of high‐intensity fire regimes, via their litter and bark fuels, is restricted to the forests of the continent's southern and eastern extremities. Our analysis suggests that the foremost driver of fire regimes at the continental scale is not productivity, as postulated conceptually, but the latitudinal gradient in summer monsoon rainfall activity.